Электромагнитное воздействие на угольный пласт для активации процесса дегазации - Алексеев, А.Д.; Кириллов, А.К.; Мнухин, А.Г.; Брюханов, А.М. (Физико-технические проблемы горного производства, 2006)
Дано теоретичне обґрунтування та методику експериментів з впливу високочастотного електромагнітного поля на вугільну речовину для прискорення десорбції метану. The theoretical substantiation and technique of experiments on effect by the high-frequency electromagnetic field with the purpose to speed up methane desorption from coal substance is given.